Elliptic model for evaluation of tumble turn in swimming - Nomura, T.; Goya, T.; Tanigawa, T. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
The purpose of this study was to evaluate of the tumble turn in swimming based on an elliptical model. Fifteen junior male swimmers were asked to perform 15 m round trip crawl including a tumble turn as fast as possible. A side view of the turn was analysed by the 2D-DLT algorithm. The trajectory of the head during the rotation phase was approximated by an elliptic model (r >= 0.90). The correlation between the elliptic indices and 15 turn properties were calculated. These elliptic indices were as follows: the inclination showed 65.9 ± 7.0 deg, the major axis indicated 0.51 ± 0.08 m, and the minor axis was 0.34 ± 0.10 m. The inclination significantly correlated with the 15m turn-out time 7.72 ± 0.36 sec (r = 0.795, p < 0.01). The minor axis significantly correlated with the 3 m turn-in time 2.21 ± 0.12 sec (r = 0.569, p < 0.05). lt was suggested that a shallower inclination and flattened of the elliptic trajectory of the head during the rotation phase had advantageous to turn performance.